High Expression Hampers Horizontal Gene Transfer - Park, Chungoo (Oxford University Press, 2012)
Horizontal gene transfer (HGT), the movement of genetic material from one species to another, is a common phenomenon in prokaryotic evolution. Although the rate of HGT is known to vary among genes, our understanding of the cause of this variation, currently summarized by two rules, is far from complete. The first rule states that informational genes, which are involved in DNA replication, transcription, and translation, have lower transferabilities than operational genes. The second rule asserts that protein interactivity negatively impacts gene transferability. Here, we hypothesize that high expression hampers HGT, because the fitness cost of an HGT to the recipient, arising from the 1) energy expenditure in transcription and translation, 2) cytotoxic protein misfolding, 3) reduction in cellular translational efficiency, 4) detrimental protein misinteraction, and 5) disturbance of the optimal protein concentration or cell physiology, increases with the expression level of the transferred gene. To test this hypothesis, we examined laboratory and natural HGTs to Escherichia coli. We observed lower transferabilities of more highly expressed genes, even after controlling the confounding factors from the two established rules and the genic GC content. Furthermore, expression level predicts gene transferability better than all other factors examined. We also confirmed the significant negative impact of gene expression on the rate of HGTs to 127 of 133 genomes of eubacteria and archaebacteria. Together, these findings establish the gene expression level as a major determinant of horizontal gene transferability. They also suggest that most successful HGTs are initially slightly deleterious, fixed because of their negligibly low costs rather than high benefits to the recipient.